PENGARUH KEPEDULIAN SOSIAL KEDISIPLINAN DAN KREATIVITAS TERHADAP SKOR NILAI PENDIDIKAN KARAKTER SISWA DI SMP NEGERI 1 SELOMERTO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to determine the effect of: (1) the perception of social care behavior, discipline and creativity on score value character education together. (2) Social awareness partially on score value character education. (3) Discipline partially on score value character education. (4) Creativity partially on score value character education. This research was conducted at Junior High School 1 Selomerto Wonosobo.This research is quantitative study using a survey method. The subjects of this study were students of Junior High School 1 Selomerto district. Wonosobo totaling 210 respondents. This study used a test sample, data collection in this study using a questionnaire. Data analysis techniques in this study using multiple regression with three predictors. Hypothesis Testing is jointly carried out using the F-test. Contribution together effectively obtained from the analysis of the coefficient of determination multiplied by the value of the standardized Beta Coefficient Zero-order Correlation multiplied by 100% for each independent variable.The result shower that (1) social care discipline and creativity together effect the score values of character education with a very small contribution is 4.20%, the higher the social care, discipline and creativity with the same, the higher the score values of character education (2) social care independently effect the score values of character with effective contribution of 0.17%, the higher the value so the higher score social care values character education (3) discipline effect the score values of character education with the effective contribution of 3.26%, the better discipline so the better of the values of character education (4) creativity independently effect the values of character education with effective contribution of 0.77%, the higher creativity of the students, the values of character education will be higher to.